Advancing Sustainable Finance: A Framework for Strategic Institutional Financing - Md Ariffin, Khadijah; Sani Inusa Milala, (Research in Management of Technology and Business, 2023)
Promoting sustainable finance has emerged as a pivotal endeavor in the modern global landscape, driven by the urgency of addressing pressing environmental and social challenges. The pursuit of sustainable finance stands as a pivotal priority in contemporary global discourse, driven by the urgency of addressing critical environmental and social challenges. This paper presents an incisive framework for advancing sustainable finance through the lens of a systematic literature review.  After employing the systematic literature review 73 scholarly article was utilized from 7 database where lit map software was employed to explore the relevant articles using seeding method. The paper uncovers insights from prior literature, outlining both successful strategies (ESG integration, impact measurement, collaborative partnerships) and ongoing challenges (data quality, greenwashing, regulatory uncertainty, resistance to change, risk assessment complexity, lack of standardization, conflicting short and long-term goals) in embedding sustainability into institutional financing. Central to the paper is a meticulously designed Framework for Strategic Institutional Financing, offering guidance through sustainable finance complexities. This blueprint includes ESG assimilation, robust risk assessment methods, stakeholder collaborations for amplified impact, and a steadfast commitment to measuring enduring outcomes, accompanied by strategic insights derived from literature to address hurdles encountered in prior framework implementations.In conclusion, this paper underscores the exigency of strategic institutional financing as a linchpin in propelling sustainable finance. Anchored in the scaffold of systematic literature review, and buttressed by the distilled wisdom of existing research, this paper emerges as an indispensable resource for institutions poised to synchronize financial objectives with abiding environmental and social advancements.